التفكير الإيجابي وعلاقته بالثقة بالنفس والطموح الاكاديمي لتلاميذ المرحلة الإعدادية - صقر، السيد أحمد محمود; جندي، أحمد عادل عبدالرازق سليمان; أبو شقة، سعدة أحمد إبراهيم (جامعة كفر الشيخ - كلية التربية, 2019)
هدف البحث الحالي إلى التعرف على العلاقة بين التفكير الإيجابي والثقة بالنفس لتلاميذ المرحلة الإعدادية، والعلاقة بين التفكير الإيجابي والطموح الأكاديمي لتلاميذ المرحلة الإعدادية، وتم استخدام المنهج الوصفي حيث يتناسب مع أهداف البحث، وتكونت عينة البحث من (٢٤٠) تلميذ وتلميذة من تلاميذ الصف الثاني الإعدادي (٩٢ تلميذ و ١٤٨ تلميذه)، وتمثلت أدوات البحث في مقياس للتفكير الإيجابي (إعداد الباحث)، ومقياس للثقة بالنفس (إعداد الباحث)، ومقياس للطموح الأكاديمي (إعداد الباحث)، وتوصل البحث إلى عدة نتائج منها: وجود علاقة موجبة ذات دلالة إحصائية بين التفكير الإيجابي وكلأ من الثقة بالنفس والطموح الأكاديمي لتلاميذ المرحلة الإعدادية.
The aim of the current research was to identify the relationship between positive thinking and self-confidence of the students in the preparatory stage, and the relationship between positive thinking and academic ambition of the students in the preparatory stage. The descriptive approach was used in accordance with the research objectives. The sample consisted of (240) students in the second grade (92 Male and 148 Female). The research tools were a measure of positive thinking (researcher preparation), a measure of self-confidence (researcher preparation) and a measure of academic ambition (researcher preparation). The research reached several results, including: a statistically significant positive correlation between positive thinking and both self-confidence and academic ambition of the students in the preparatory stage.
Keywords: السياسة التعليمية -- التعليم الإعدادي -- طلاب المرحلة الإعدادية -- الصحة النفسية -- الثقة بالنفس -- التفكير الإيجابي -- الطموح الأكاديمي